2021
DOI: 10.12688/f1000research.31645.2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of bacterial co-infection among moderate, severe and critically ill COVID-19 patients in the second referral hospital in Surabaya

Abstract: Background: Data on the prevalence of bacterial co-infections among COVID-19 patients are limited, especially in our country, Indonesia. We aimed to assess the rate of bacterial co-infections in hospitalized COVID-19 patients and report the most common microorganisms involved and the antibiotic use in these patients. Methods: This study is a retrospective cohort study, among COVID-19 adult patients admitted to Universitas Airlangga Hospital Surabaya from 14 March-30 September 2020. The bacterial infection is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 24 publications
(37 reference statements)
2
26
0
5
Order By: Relevance
“…This proportion is higher than that reported in the United Kingdom (UK) (85.2%), 26 Netherland (60.1%), 10 and Surabaya Indonesia (75.3%). 27 In fact, microbiological testing showed that the bacterial infection and co-infection among hospitalized COVID-19 patients was infrequent. 10 Several studies reported 1.25 % of 925 patients, 10 19.7% of 218 patients, 27 1107 of 48902 patients were confirmed bacterial co-infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This proportion is higher than that reported in the United Kingdom (UK) (85.2%), 26 Netherland (60.1%), 10 and Surabaya Indonesia (75.3%). 27 In fact, microbiological testing showed that the bacterial infection and co-infection among hospitalized COVID-19 patients was infrequent. 10 Several studies reported 1.25 % of 925 patients, 10 19.7% of 218 patients, 27 1107 of 48902 patients were confirmed bacterial co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…27 In fact, microbiological testing showed that the bacterial infection and co-infection among hospitalized COVID-19 patients was infrequent. 10 Several studies reported 1.25 % of 925 patients, 10 19.7% of 218 patients, 27 1107 of 48902 patients were confirmed bacterial co-infection. In COVID-19 patients in the UK, the most frequent etiology of respiratory co-infection was Staphylococcus aureus and Haemophilus influenza, of secondary respiratory infection was Enterobacteriaceae and S aureus, and in bloodstream infection was Escherichia coli and S aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, the information of incidence and prevalence of bacterial infections in COVID-19 patients has not been widely reported (Prasetyoputri, 2021). However, based on a retrospective study at the Airlangga University Hospital, Surabaya conducted by Asmarawati et al (2021), it was stated that there 19.7% of moderate and critically ill patients had bacterial infections. Those bacterial infections impacted the increase of hospitalization length, high risk of respiratory failure, use of ventilators, and ICU admission.…”
Section: Berkala Penelitian Hayati |mentioning
confidence: 99%
“…5). The antibiotics used are quinolones (moxifloxacin and levofloxacin), cephalosporin (ceftazidime, cefotaxime, ceftriaxone, cefuroxime, and cefoperazone-sulbactam), a carbapenem (meropenem), and levofloxacin (Asmarawati et al, 2021).…”
Section: Antibioticsmentioning
confidence: 99%